Education and equality of opportunity: What have we learned from educational reforms? - Helena Holmlund (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2016)
Equality of opportunity has been one of the central ideas governing education policy in the Nordic welfare state. This paper takes its starting point in the shared history of educational reform in the Nordic countries, and presents evidence that the comprehensive school reforms that implied a shift from selective two-tier schooling systems to unified compulsory schools were beneficial for equality of opportunity. This evidence is compared to a choice and voucher reform that in the 1990's introduced pedagogical as well as organizational variety in the education system in Sweden. The Swedish choice reform is unique in an international perspective, and has reshaped the education sector dramatically as a growing number of pupils attend non-public independent schools. The current education debate shows a widespread concern that the introduction of choice has led to a backlash for equality of opportunity. Parental background remains a strong determinant of pupil performance. However, recent research finds no indication that family background has become more important over time in explaining pupil outcomes. The Swedish education system nevertheless faces a number of challenges if it is to level the playing field and create equal opportunities for all pupils: schools are becoming increasingly more segregated, much as a consequence of immigration, and disadvantaged pupils are less likely to exercise school choice compared to their more advantaged peers.
Keywords: I20; I24; 330; educational reform; equality of opportunity; Bildungsreform; Bildungschancen; Wirkungsanalyse; Bildungspolitik; Nordeuropa